A militarização das escolas públicas em Goiás: uma reflexão sobre o processo de ensino e cidadania na militarização do colégio Estadual Nivo das Neves. - Nunes, Marcelo Vaz (Universidade Federal de Catalão, 2022)
This research aimed to reflect on the expansion of the militarization of public schools in Goiás, analyzing the historical context in the implementation of the model in the Colégio Estadual Nivo das Neves and the transformations that the teaching unit suffered from the creation of a new unit of CEPMG , an experience I experienced for two years (2016-2018) and which led us to the need to know this process and bring reflections on the proposed model of training in these schools to the public debate. Pandemic times redirected the research to a documentary analysis through sources such as newspapers, magazines, articles and dissertations by authors such as: Cibele de Souza; Leandra Augusta de Carvalho Moura Cruz; Neuza Souza Rego Ferreira, Miriam Fábia Alves and others, which deal with the theme of militarization of schools in Goiás. This model of military management was created in 1999, later expanded throughout the State, reaching the number of 60 (sixty) units, transforming it into the main political action for education in the PSDB governments in Goiás, gaining national projection and greater visibility with the context of the political-civilian and media coup that resulted in the impeachment of President Dilma Rousseff and paved the way for authoritarianism and neoliberal ideas in education, such as the attempt to privatize education, through the implementation of Social Organizations (O.S). Resistance to this neoliberal wave resulted in strikes by education professionals and in the process of occupation of public schools by high school students in 2015, leading education to the central axis of political polarization, paving the way for reactionary ideas such as the School without Party and the militarization of schools, inspired by the model of Goiás and other states, became a national project after the election of Jair Messias Bolsonaro, contrary to all curricular documents and educational legislation that emphasizes democratic formation, on the other hand, we also analyze the process occupation of schools by high school students that occurred concomitantly with reactionary and privatist attacks on education, the pedagogical experience carried out by students, demonstrated a model opposed to training and citizenship proposed by the military model, leading to reflection on the democratic values intended in the curricular documents and in legislation and the rgent need to demilitarize schools.
The militarization of public schools in Goiás: a reflection on the teaching and citizenship process in the militarization of the Nivo das Neves State School.
Keywords: Militarização; Autoritarismo; Democracia; Cidadania